2023
DOI: 10.18280/ijsse.130105
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Digitalization on the Innovative Strategy of the Industrial Enterprises Development in the Context of Ensuring Economic Security

Abstract: The purpose of the article is to study the impact of digitalization on the innovative strategy of the enterprise development in the context of ensuring economic security. Within the article, peculiarities of the digitalization development in Ukraine are examined. The main obstacles that hold back the development of innovative technologies and digital platforms in Ukraine are identified. The problems of the country's industrial development and the difficulties of implementing the principles of the digital econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Overall, the impact of digitalization is positive on the demographic dividend, contributing to a more educated, productive, and innovative working-age population, which is essential for sustained economic growth. Our results aligned with the studies by (Alam, 2009;Gautam et al, 2021;Hosan et al, 2022;Popelo et al, 2021;Sarker et al, 2021).…”
Section: Long Run Analysissupporting
confidence: 93%
“…Overall, the impact of digitalization is positive on the demographic dividend, contributing to a more educated, productive, and innovative working-age population, which is essential for sustained economic growth. Our results aligned with the studies by (Alam, 2009;Gautam et al, 2021;Hosan et al, 2022;Popelo et al, 2021;Sarker et al, 2021).…”
Section: Long Run Analysissupporting
confidence: 93%
“…Having identified the key factors regarding the development of private and public universities in the European Union, the question arises: what is the advantage of Open Universities? First of all, open universities have a much simpler admission procedure; they require a free package of documents, not clearly regulated by the education system, but determined privately by each university (Kychko, 2021). For instance, it is enough to have an international passport and a document about any education obtained (even private in special schools) or attending training, and you have the opportunity to be enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to be noticed that the meta-analysis of the literature study by Galina and Xu (2016) finds a higher possibility for adverse effects of FDI in countries with low-skilled workers, which is the case of developing economies. It is also noteworthy to consider the case of developed economies where a few studies have observed the notable impacts of FDI inflows (Santiago, 1987;Zhao, 1998) as well as digitalization (Eichhorst et al, 2017;Popelo et al, 2021) on the prospects of employment, also from other aspects (Narayan and Smyth, 2005).…”
Section: Discussionmentioning
confidence: 99%